The Cost of the Gluten-Free Diet: Household Food Expenditures in Families With a Child or Adolescent With Celiac Disease. (1st June 2016) - Alzaben, A; Mager, D; Turner, J; Marcon, M; Anders, S
Abstract: BACKGROUND: Celiac disease (CD) is a digestive disease that is caused by an immune reaction to the protein gluten. The gluten free diet (GFD) is the only treatment for CD. In 2012, the sale of GF processed foods reached up to $460million in Canada; an increase in 25% since 2008. Despite being the fastest growing food intolerance category in Canada, GFD consumers face challenges from various voluntary GF-labelling schemes and limited retail and food-service product options. OBJECTIVES: To estimate GF-food expenditure patterns for affected families with children or adolescents with CD to identify the cost burden of following a GFD and compared against non-GFD Canadian families. DESIGN/METHODS: A pilot study was conducted in families with a child with biopsy proven CD following the GFD (n=15; 10±3 years) and attending a GI/CD clinic. Family Socio-demographics (age of parents, number of children/number of members following GFD in households) and the receipts of food purchases over a one-month period were obtained from parents/caregivers. The cost of GFD was analyzed as "actual food costs on related receipts" and determined as total GFD cost (per household/per child with CD) basis. The result of this study was compared against average incomes and food expenditures of Canadian households as reported by Statistic Canada in 2013. RESULTS: The mean age of the parents of child with CD was (44±5 years) and the mean number of children in households was 2.0±0.6. The average duration of following GFD was 4±2 years (age at diagnosis 6±2 years). The median income for Canadian family and for family with children with CD was C$ 84, 000/year and C$ 100, 000/year, respectively. The average food expenditure was C$ 842/month for the average Canadian household with children vs C$ 1105±393/month for comparable Canadian households affected by CD. The amount of money spent on GF packaged foods was C$ 145±100/month. The average food expenditure of GF food and gluten containing food was C$112±72/child/month (+GF) and C$ 29±14/house-hold member/month (-GF), respectively. CONCLUSION: Total food expenditures in families with a child/adolescent with CD are higher than the Canadian averages. This has implications on economic access and adherence to GFD in children/adolescents with CD. CD and proper dietary adherence to GFD guidelines poses significant economic burdens on affected families. These results and unanswered questions of economic access, affordability and quality of life hold several Canadian policy implications.